DESIGN AND DEVELOPMENT OF RIVER WATER QUALITY MONITORING AND SALINITY DEVELOPMENT PROPERLY REALTIME BASED IoT - Ikhwan, Sulthonik; Marindani, Elang Derdian; Jati, Dian Rahayu (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
The decline in raw water quality recorded by PDAM Pontianak on Jalan Imam Bonjol is caused by sea water intrusion across land during the dry season. The research objective is to design an IoT-based system as a data transmission medium for monitoring river water quality, the water pH sensor for reading pH levels of water and the Turbidity sensor for reading the level of turbidity in river water and can designing a river water quality monitoring tool using several parameters, namely salinity, pH levels and turbidity. From the overall test results of the tool it can be concluded that the tool has worked. The tool's measurement results can be seen in the Blynk application sent by the tool at an average interval. The results of measurements at 2 locations for 3 days showed that TDS ranged from 2 ppm to 6.16 ppm with an average of 3.8 ppm, turbidity ranged from 211 NTU to 574 NTU with an average of 424.4 NTU and pH ranged from 6.87 to 8.62 with an average -average of 8.02. The tool designed is capable of sending measurement data via the Blynk application to smartphone users.